The clinical application of metagenomic next-generation sequencing in infectious diseases at a tertiary hospital in China - Wang, Chuwen; Yan, Danying; Huang, Jiajia; Yang, Naibin; Shi, Jiejun; Pan, Shou; Lin, Gaoqiang; Liu, Ying; Zhang, Yingying; Bian, Xueyan; Song, Qifa; Qian, Guoqing (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Compared to traditional diagnostic methods, rapid diagnostic methods for infectious diseases are urgently needed. Metagenomic next-generation sequencing (mNGS) has emerged as a promising diagnostic technology for clinical infections. Methods: This retrospective observational study was performed at a tertiary hospital in China between May 2019 and August 2022. The chi-square test was used to compare the sensitivity and specificity of mNGS and traditional diagnostic methods (TDMs). We also performed a subgroup analysis of the different pathogens and samples. Results: A total of 435 patients with clinical suspicion of infection were enrolled and 372 (85.5%) patients were finally categorized as infectious disease (ID) group. The overall sensitivity of mNGS was significantly higher than that of the TDMs (59.7% vs 30.1%, P < 0.05). However, there was no significant difference in overall specificity between the two methods (83.3% vs 89.6%, P = 0.37). In patients with identified pathogens, the positive rates of mNGS for detecting bacteria (88.7%), fungi (87.9%), viruses (96.9%), and Nontuberculous mycobacteria (NTM, 100%) were significantly higher than those of TDMs (P < 0.05). The positive rate of mNGS for detecting Mycobacterium tuberculosis (MTB) was not superior to that of TDMs (77.3% vs 54.5%, P = 0.11). The sensitivities of mNGS for pathogen identification in bronchoalveolar lavage fluid (BALF), blood, cerebrospinal fluid (CSF), pleural fluid, and tissue were 72.6%, 38.7%, 35.0% and 80.0%, respectively. Conclusion: With the potential for screening multiple clinical samples, mNGS has an overall advantage over TDMs. It can effectively identify pathogens, especially those that are difficult to identify using TDMs, such as NTM, chlamydia, and parasites.